Strategy for Implementing Machine Point of Sale in Merangin Regency - Nimiyati; Hidayat, Rahmat; Rahman, Abdul (Journal of Indonesian Rural and Regional Government, 2025)
The implementation of the Machine Point of Sale (MPOS) system in Merangin Regency represents part of the local government’s efforts to enhance accountability and effectiveness in regional tax collection. However, its implementation in the field has not yet reached optimal levels. This study is motivated by the low utilization rate of MPOS among taxpayers, as well as various technical and non-technical challenges. The purpose of this research is to evaluate the effectiveness of MPOS implementation, identify existing obstacles, and formulate appropriate development strategies using a SWOT analysis approach. This study employs a qualitative descriptive method, with data collected through interviews, observation, and document analysis. The findings indicate that although MPOS has contributed to improving tax compliance, its application remains partial and uneven among taxpayers. Challenges such as limited taxpayer understanding, unresponsive devices, and insufficient training for operators continue to hinder effective implementation. Based on the SWOT analysis, the strategic position falls into Quadrant II with an IFAS score of 0.75 and an EFAS score of -0.20, suggesting the need for a diversification strategy. The local government is advised to leverage internal strengths, such as human resources and infrastructure readiness, to address external threats—particularly by building public trust and increasing taxpayer awareness. This study recommends strengthening training programs, improving MPOS device functionality, and adopting a more responsive and educational service approach.